BARATAYUDA SULUHAN GATUTKACA GUGUR SEBAGAI PAHLAWAN : KAJIAN DARI ASPEK ETIS DAN ESTETIS (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
Puppet show is part of Indonesian culture that teaches good conducts. In Javanese puppet world, Mahabarata story has many times been transformed in puppet plays. Baratayuda Suluhan is one of the episodes of great battle between Kurawa against Pandawa in Kurusetra battlefield, in which Gatutkaca plays role as the commander in chief. The show of Baratayuda series took place in Taman Budaya Jawa Tengah of Surakarta on every Friday Kliwon eves, Javanese date, that has been lasting for almost two years. The shows are based on the puppet maters’ (dalang) point of views so that, sometimes, they seem not in the right order and tend to follow the dalangs’ tastes. Suluhan play is often known as the Dead of Gatutkaca. After the death of Bisma, the knights of Kurawa obeyed Darmayuda’s rule no more. The rule was about war ethics. The battle between Kurawa and Pandawa occurred heroically, severely, cruelly and ruthlessly. They fought nights and days. The most important thing for the commander in chief was how to defeat the enemy and how to kill even when they broke the rule of war. They never stopped fighting. Baratayuda Suluhan is performed at night by usingtorch or suluh as the lamp. Gatutkaca died as a hero. There are ethics values that can be generated from the battle of Baratayuda Suluhan as the moral values. All characters dying in the battle have ethics judgments according to the perspective of Javanese supporting puppet show. Kata kunci: pertunjukan wayang, etika , Baratayuda, pahlawan, sanggit